Optimizing Mixtures of Alkali Aluminosilicate Cement Based on Ternary By-Products - Hoang Vinh Long (Civil Engineering Journal, 2021)
Portland cement is a popular binder but causes many adverse effects on the environment. That is due to the large consumption of raw materials and energy during production while emitting vast amounts of CO2. In recent years, Alkali Aluminosilicate Cement (AAC) has drawn much attention in research and development and promises to become a binder that can replace the traditional cement. In many studies of this binder, the content of the ingredients is often gradually changed to determine the optimal composition. The object of this paper is to optimize the composition of AAC using a combination of three by-products as the primary raw material, including Rush Husk Ash (RHA), Fly Ash (FA), and Ground Granulated Blast-Furnace Slag (GGBS). The investigation was conducted based on the critical parameter SiO2/Al2O3, and the D-optimal design. The FA and the GGBS were industrial product form, while the RHA was ground in a ball mill for 2 hours before mixing. The results show that this type of binder has setting time and soundness to meet standard cement requirements. While comparing to Portland cement, the AAC has a faster setting time, slower development of compressive strength in the early stages but a higher strength at the age of 56 days. According to the highest compressive strength at 28 days and high fly ash content, the optimal composition was RHA of 27.8%, FA of 41.8%, and GGBS of 15.4%, corresponding to the ratio SiO2/Al2O3 of 3.83. In addition, compressive strength at 28 days of the mortar specimens with the optimal binder and the ratio of water/ cement at 0.32 reached 63 MPa. Doi: 10.28991/cej-2021-03091724 Full Text: PDF